THE POTENTIAL OF STEM CELL THERAPY AS A MANAGEMENT OF CHRONIC PAIN: A SYSTEMATIC REVIEW - Putu Yogi Pramana; Agung Bagus Sista Satyarsa; Ida Ayu Sri Wijayanti; Anak Agung Raka Sudewi (MNJ (Malang Neurology Journal), 2023)
Background: Stem cells has previously been used with promising results as a therapeutic modality for neurodegenerative diseases and pain but has recently been introduced as a treatment for chronic pain. Objective: This study aims to review the available literature on the role of stem cell therapy as a treatment for chronic pain. Methods: A review of clinical reports using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method published in Pubmed, EMBASE (Excerpta Medica Database), and ScienceDirect were used from 2013 to 2023, and The search tool was used to locate and enroll patients for ongoing, presently active clinical studies. The search terms used included “chronic pain,” “therapy,” “prosedure” “neuropathic,” “discogenic,” “modality,” “musculoskeletal” and “stem cell.” The research was then carried out to assess the quality of the study using the Critical Appraisal Skills Program questionnaire. Results: There were around 186 studies related to the keyword, and only about 11 studies that met the inclusion criteria included in this article were obtained. Based on the results of the study, it was found that the role of stem cell therapy in the form of MSC and ADS, which was used, had a significant effect as a chronic pain therapy in patients. A decrease in the quality of pain was obtained based on VAS (Visual Analog Scale), ODI (Oswestry Disability Index), and NRS (Numeric Rating Scale) assessments as well as an increase in patient function. Conclusion: Although current research suggesting the use of mscs as a novel therapy method for disc, neuropathic, and musculoskeletal pain, further studies are required to demonstrate the efficacy as well as security of this modality